2014
DOI: 10.1097/mcg.0b013e3182a8a254
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Invasion in Hepatocellular Carcinoma

Abstract: MaVI represents a distinct tumor phenotype of HCC and is associated with younger age, aggressive tumor behavior, poor liver functional reserve, and poor performance status. It adversely affects the survival of HCC patients independent of treatment strategy. Intensive anticancer therapy should be proposed to achieve a better long-term survival for the at-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…Vascular invasion was defined as the presence of a thrombus adjacent to the tumor in the portal system or the hepatic vein system with a vague boundary confirmed by at least two imaging modalities [40]. The clinical and radiological data, including age, gender, white blood cell counts (WBC), platelet counts (PLT), neutrophil counts, lymphocyte counts, AFP levels, alanine transaminase (ALT) levels, aspartate aminotransferase (AST) levels, total bilirubin (TBIL) levels, indirect bilirubin (IBIL) levels, alkaline phosphatase (ALP) levels, albumin (ALB) levels, C-reactive protein (CRP) levels, hepatitis B surface antigen (HbsAg) levels, hepatitis B virus deoxyribonucleic acid (HBV-DNA) load, tumor size, tumor number and vascular invasion, were collected and analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Vascular invasion was defined as the presence of a thrombus adjacent to the tumor in the portal system or the hepatic vein system with a vague boundary confirmed by at least two imaging modalities [40]. The clinical and radiological data, including age, gender, white blood cell counts (WBC), platelet counts (PLT), neutrophil counts, lymphocyte counts, AFP levels, alanine transaminase (ALT) levels, aspartate aminotransferase (AST) levels, total bilirubin (TBIL) levels, indirect bilirubin (IBIL) levels, alkaline phosphatase (ALP) levels, albumin (ALB) levels, C-reactive protein (CRP) levels, hepatitis B surface antigen (HbsAg) levels, hepatitis B virus deoxyribonucleic acid (HBV-DNA) load, tumor size, tumor number and vascular invasion, were collected and analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…[25] Moreover, patients with vascular invasion have a high frequency of fatal recurrence, multiple intrahepatic tumors, and extrahepatic metastasis. [6] In theory, due to the rich blood supply in HCC, treatment with PA-TACE might kill or decrease the remaining tumor cells, eliminate micro-metastases to some extent, and improve long-term survival outcome. Our study suggested that vascular invasion and larger tumor diameter in HCC patients are more important and stronger risk factors for predicting prognosis, although PA-TACE could partially improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…[45] In addition, MVI displays aggressive tumor behavior and is closely correlated with larger tumor burden. [6] However, there is still no recommended postsurgical treatment strategy for HCC patients with MVI, which renders the postsurgical management of these patients a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementally, identification of the stage of tumor is based on the tumor–node–metastasis (TNM) classification system which was promulgated by the American Joint Committee on Cancer and International Union Against Cancer in 2010 [38] and Barcelona-Clinic-Liver-Cancer (BCLC) stages [39]. Vascular invasion was recognized by the presence of thrombus adjacent to the tumor in portal and hepatic vein system with vague boundary confirmed by at least two imaging modalities [40]. Routine chest CT scan was performed to detect metastatic lesion(s).…”
Section: Methodsmentioning
confidence: 99%